THE PRICE AND ISLAMIC SERVICE QUALITY ON CUSTOMER SATISFACTION IN ISLAMIC BANKING - Krisnanda Krisnanda; Linda Putri Nadia; Affan Wazzar Achmad; Ahmad Mukhlisin (I-Economics: A Research Journal on Islamic Economics)
The rapid growth of Bank Syariah Indonesia in recent years has strongly emphasized the importance of pricing and Islamic service quality in gaining a competitive advantage. This research aims to analyze the influence of price and Islamic service quality on customer satisfaction of Bank Syariah Indonesia in Kudus. The study employs the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to examine the conceptual framework. Data were collected from 140 Indonesian Islamic banking customers in Kudus using questionnaires. The analysis findings confirm that both price and Islamic service quality positively and significantly impact customer satisfaction in Bank Syariah Indonesia. Competitively priced products and services, aligned with Islamic principles, play a pivotal role in creating customer satisfaction.